A comparison of behaviour and habitat use by Bewick - Peihao, Cong; Rees, Eileen C; Meng Meng, Sun; Meijuan, Zhao; Lei, Cao; Barter, Mark; Fox, Anthony D (Wildfowl, 2013)
The dynamics and behaviour of the Northwest European population of Bewick’s Swans Cygnus columbianus bewickii has been studied over several decades, yet relatively little is known about the more numerous Eastern population of the species. Comparisons of the two populations could help explain why the Northwest European population is in decline. Here we describe for the first time the swans’ use of a wintering site (Shengjin Lake) in China, comparing these findings with studies made of Bewick’s Swans wintering at Slimbridge, UK. First birds arrived in late October at both sites, and swans remained at Shengjin Lake until late March, which approximates to the time that Bewick’s Swans spend at wintering sites across Europe. Monthly swan counts did not correlate significantly with water level variations at Shengjin Lake (and by implication food accessibility). However, more extensive monitoring, both of water depth and food abundance, is required to understand whether fluctuating water levels affect site use by the birds. There was no significant difference between the two sites in the proportion of birds recorded feeding throughout the day, though this may reflect a high level of variance in the swans’ feeding activity. A bimodal pattern in feeding activity recorded for the swans in China is similar to feeding patterns recorded for Bewick’s Swans at Slimbridge. Breeding success recorded for Bewick’s Swans in the Eastern population was significantly higher than for those in the Northwest European population every year from 2007 to 2010 inclusive. Further studies should investigate whether this is attributable to the carry-over effects of swans in the Eastern population feeding on aquatic vegetation in traditional wetland habitats during winter, as opposed to the farmland used by swans wintering in Europe.